Karakterisasi Protein Sorgum dan Upaya Peningkatan Jejaring Protein Sorgum Dengan Penambahan Glukosa-Oksidase [Characterization of Sorghum Protein and Improvement of Sorghum Protein Net-Working with Addition of Glucose-oxidase] - Endah Wulandari (Universitas Pelita Harapan, 2018)
Sorghum (Sorghum bicolor (L.) Moench) contains about 10% protein so it can act as a source of protein. Kafirin is a protein in sorghum distinguished on Î±, Î², and Î³-kafirin based on molecular weight differences, ease of extracting, and molecular structure. Characteristics of the sorghum protein and the ability of glucose-oxidase will form a protein network naturally between proteins or peptides resulting in polymerization. The objectives of the research were to fractionate protein of the flour of Zh-30 sorghum strain using five types of solvents. The protein fractions were analyzed for protein content and molecular weight by SDS-PAGE and evaluated for protein-network formation by glucose-oxidase, the result showed that flour protein of the sorghum Zh-30 strain consisted of five classes of proteins with a ratio of respectively albumin, globuline, kafirin 1, gluteline and kafirin 2 or cross-linked kafirin 11:11:42:7:29. Kafirin 1 content was 36.01%, kafirin 2 24.79%, gluteline 22.15%, globuline 12.81% and albumin 4.24% of total protein. Molecular weight of each protein fraction of the sorghum flour Zh-30 strain was respectively albumin 69.9 kDa, kafirin 1 which consisted Î±1-kafirin 22.4 kDa and Î±2-kafirin 23.5 kDa, globuline 121 kDa, gluteline 15.5 kDa and kafirin 2 which consisted of Î±1-kafirin 16.2 kDa, Î±2-kafirin 23.5 kDa, Î²-kafirin 24.6 kDa and Î³-kafirin 53.6 kDa. Protein net-working was established when the glutelin fraction was treated with glucose-oxidase (MW 69 kDa from 15.5 kDa).